2021
DOI: 10.3906/sag-2010-187
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the relationship between cranial magnetic resonance imaging findings and clinical status in children with cerebral palsy

Abstract: Background/aim: The objective of this study was to evaluate the relationship between cranial magnetic resonance imaging (MRI) findings and clinical features in cerebral palsy (CP). Methods: Children aged 3 to 18 years, who were followed with the diagnosis of CP between January 2012 and September 2015, were included. The type of CP was classified using the European Cerebral Palsy Monitoring Group's classification system and then, patients were divided into two groups as spastic or non-spastic groups. The Gross … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
0
0
Order By: Relevance
“…15,16 A Turkish cohort showed PVL as the commonest finding in 33% patients followed by cerebral atrophy (12.9%), migration anomaly (9.7%), cerebellar involvement (3.2%) and basal ganglion involvement in 4 cases (6.4%). 17 Our study results were in accordance with this published data except brain malformations which were found to be rare in our study population. A south African study concluded basal ganglion lesions as most frequent in 27.6% study population however PVL and cystic encephalomacia were found in only 3.6 and 7.8% patients respectively.…”
Section: Discussionsupporting
confidence: 93%
“…15,16 A Turkish cohort showed PVL as the commonest finding in 33% patients followed by cerebral atrophy (12.9%), migration anomaly (9.7%), cerebellar involvement (3.2%) and basal ganglion involvement in 4 cases (6.4%). 17 Our study results were in accordance with this published data except brain malformations which were found to be rare in our study population. A south African study concluded basal ganglion lesions as most frequent in 27.6% study population however PVL and cystic encephalomacia were found in only 3.6 and 7.8% patients respectively.…”
Section: Discussionsupporting
confidence: 93%
“…Cognitive/intellectual disability was uncommon in diplegia because it generally did not damage brain gray matter. In contrast, epilepsy and cognitive/intellectual disability were more common and severe in quadriplegia because of extensive brain injury (36). Although cognitive/intellectual disability is more common in children with CP with severe brain injury, and the possibility of seizures is higher, some children with severe brain injury have normal intelligence and do not often accompany by epilepsy.…”
Section: Discussionmentioning
confidence: 97%